High-Speed Digital Imaging of Ependymal Cilia in the Murine Brain - Lechtreck, Karl-Ferdinand (2009)
The development and health of mammals requires proper ciliary motility. Ciliated epithelia are found in the airways, the uterus and Fallopian tubes, the efferent ducts of the testes, and the ventricular system of the brain. A technique is described for the motion analysis of ependymal cilia in the murine brain. Vibratome sections of the brain are imaged by differential interference contrast microscopy and recorded by high-speed digital imaging. Side views of individual cilia are traced to establish their bending pattern. Tracking of individual cilia recorded in top view allows determination of bend planarity and beat direction. Ciliary beat frequency is determined from line scans of image sequences. The capacity of the epithelium to move fluid and objects is revealed by analyzing the velocity of polystyrene beads added to brain sections. The technique is useful for detailed assessment of how various conditions or mutations affect the fidelity of ciliary motility at the ependyma. The methods are also applicable to other ciliated epithelia, for example, in airways.